The common murre (Uria aalge), an auk seabird, reacts to underwater sound - Anderson Hansen, Kirstin; Hernandez, Ariana; Mooney, T. Aran; Rasmussen, Marianne H.; Sørensen, Kenneth; Wahlberg, Magnus (The Journal of the Acoustical Society of America, 2020)
Marine mammals have fine-tuned hearing abilities, which makes them vulnerable to human-induced sounds from shipping, sonars, pile drivers, and air guns. Many species of marine birds, such as penguins, auks, and cormorants, find their food underwater where light is often limited, suggesting sound detection may play a vital role. Yet, for most marine birds, it is unknown whether they are using, and can thereby be affected by, underwater sound. The authors conducted a series of playback experiments to test whether Alcid seabirds responded to and were disrupted by, underwater sound. Underwater broadband sound bursts and mid-frequency naval 53 C sonar signals were presented to two common murres (Uria aalge) in a quiet pool. The received sound pressure levels varied from 110 to 137 dB re 1 μPa. Both murres showed consistent reactions to sounds of all intensities, as compared to no reactions during control trials. For one of the birds, there was a clearly graded response, so that more responses were found at higher received levels. The authors' findings indicate that common murres may be affected by, and therefore potentially also vulnerable to, underwater noise. The effect of man-made noise on murres, and possibly other marine birds, requires more thorough consideration.